Foreign preschool staffs and the increasing number of bilingual children - Loque Candace Alison (2007)
I have three reasons why I am writing this paper. The first reason is to give a view of the different reasons why people come to Iceland. The second reason is to give information on how multicultural education can be useful in a multicultural preschool and the larger community. The fact that there is an active international exchange of academics and cultures through orderly acceptance of university students here in Iceland can only lead to an increase of the number of foreign teachers who will soon be part of the Icelandic work force. To be able to constructively manage conflicts and clashes of ideas in a multicultural environment there is a need for an organization to be able to improve employee productivity by constructively managing the conflict itself through understanding and applying multicultural education. A multicultural environment is an inevitable part of the educational and employment experiences of professionals. The second purpose of this paper leads me to another concern. It is to give an insight of the importance of acquiring language skills, credibility of employees, competency and social flexibility in a multicultural context. Social flexibility between staff members and the children is important. Their multicultural social interactions can provide excellent opportunities for building global professional networks.